Benefits & costs of Kyoto - Jason Shogren (Fondazione Eni Enrico Mattei (FEEM), 1999)
The 1998 Kyoto protocol signalled a new earnestness of international intent toward addressing the perceived risk of climate change. Kyoto demands that developed nations turn their economies so as to hit differentiated, sub-1990 level carbon emission targets within the next decade or so. But when thinking of the Kyoto protocol imagine trying to turn a battleship on a dime with a third of the crew on-board. Improbable, but doable...but for what benefit...and at what cost? The magnitude depends on what you choose to believe about the answer to these questions: Are we on the cusp of a catastrophe? Will developing countries ever participate? What will we do with any revenues that are raised in a trading system? Should nations be forced to reduce some fixed percentage of emissions at home? Can carbon sinks reduce costs? Will people adopt new energy-efficient technologies without a price hike in energy? The answers to these questions from economic analysis say that the catastrophes have to be exceedingly likely for Kyoto to make sense.
Keywords: H4; Q0; 330; Climate change; Benefits; Costs; Technology; Flexibility; Umweltabkommen; Treibhausgas-Emissionen; Klimawandel; Kosten-Nutzen-Analyse; Welt